Perspectives from the contested terrains of Africa: intellectualism, development and social movements - Dumisa, Siphesihle (Ciência & Trópico, 2013)
ABSTRACTThis paper discusses three crucial terrains of contestation which weave together the kaleidoscopic tapestry of Africa’s contemporary development challenges. An assessment of academic epistemologies in African Studies, development theories, and the potential of social movements who espouse alternatives for development, illustrate why Africa’s position continues to be peripheral. A twenty-first century evaluation of Africa’s relationship with the West, when paying close attention to the aspects of intellectual discourses and knowledge paradigms, at best, provides reasons for guarded optimism, and at worst, raises serious concerns for the attainment of unorthodox development in Africa. The article argues that the dominance of non-African scholars in the African intellectual space renders development in Africa to be designed according to non-African ideologies and paradigms. Whilst social movements represent a revolt against this, it is assessed that their heterogeneous nature deems them neither intrinsically nor collectively progressive. The theory of epistemic disobedience is applied as a framework to understand the agenda of orthodox development practices inherent within Modernisation. This narrative is branded as a sophism due to its historical and persistant failures on the African continent. Until these contestations are resolved in favour of African perspectives, development in Africa will continue to follow Western theories, which have hitherto borne limited success.KEYWORDS: African Studies. World Social Forum. Development alternatives.Perspectivas dos terrenos em litígio da África: intelectualismo, desenvolvimento e movimentos sociaisRESUMOO continente africano tem sido caracterizado por contestações fervorosas e conflitos violentos de diversas naturezas, desde tempos imemoriais. Este artigo discute três terrenos cruciais de contestação que tecem desafios contemporâneos do desenvolvimento da África. Uma avaliação das epistemologias acadêmicas em Estudos Africanos, teorias de desenvolvimento e o potencial dos movimentos sociais que defendem alternativas de desenvolvimento ilustram porquê a posição da África continua a ser periférica. Uma avaliação do século XXI sobre a relação da África com o Ocidente, quando prestando atenção aos aspectos de discursos intelectuais e aos paradigmas do conhecimento, na melhor das hipóteses, fornece razões para otimismo; e, na pior das hipóteses, levanta sérias preocupações para a conquista do desenvolvimento heterodoxo da África. O documento argumenta que o domínio dos estudiosos não africanos, no espaço intelectual africano, torna o desenvolvimento na África a ser projetado de acordo com as ideologias e paradigmas não africanas. Enquanto os movimentos sociais representam uma revolta contra isso, nota-se que a sua natureza heterogênea os considera nem intrinsecamente, nem coletivamente progressiva. A teoria da desobediência epistêmica é aplicada como um quadro para entender a agenda de práticas de desenvolvimento ortodoxo inerentes a modernização. Esta grande narrativa é marcada como um sofisma devido as suas falhas históricas e persistentes no continente africano. Até que essas contestações sejam resolvidas, em favor de perspectivas africanas, o desenvolvimento na África continuará a acompanhar as teorias ocidentais, que têm transmitido sucesso até então limitado.PALAVRAS-CHAVE: Estudo africano. Forum social mundial. Alternativas de desenvolvimento.